QUALITATIVE PHYTOCHEMICAL SCREENING AND ANTIOXIDANT ACTIVITY OF ELYTRARIA ACAULIS LINDAU (ACANTHACEAE) Research Article - m, Manigandan; K, Kolanjinathan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: To analyze the phytochemicals quantitatively and screening the antioxidant efficacy of methanol extracts of Elytraria acaulis plant extract by in vitro. Methods: The total phenols, flavonoids, and tannin contents analyzed by Folin-Ciocalteu method, aluminum chloride colorimetric and calculated as gallic acid equivalents/g (GAE/g) of dry weight. Free radical scavenging activity was screened using 1,1-diphenyl-2-picrylhydrazyl (DPPH), radical scavenging activities, and ferric reducing power assay was also analyzed. Results: The total phenolic content of the aqueous leaf extract was 46.84 µg GAE/g of extract powder. Significantly similar levels of total flavonoid and tannin contents of the plant were 41.72 and 39.50 µg GAE/g, respectively. The plant extracts showed appreciable free radical scavenging activities at the highest concentration of 400 µg/mL superoxide anion radical with IC values (107.7±1.081 µg/mL), and for DPPH and considerably high amount of radical scavenging activity was found with very low IC 50 50 values (4.3±0.88 µg/mL) compared with quercetin. Conclusion: The phenolic and flavonoid compounds provide substantial antioxidant properties which could be effectively used for pharmaceutical, nutraceutical as well as anti-inflammatory applications. Keywords: Phenols, Flavonoids, 1,1-diphenyl-2-picrylhydrazyl, Pharmaceuticals.